Melatonin Protects Intervertebral Disc from Degeneration by Improving Cell Survival and Function via Activation of the ERK1/2 Signaling Pathway. (2nd December 2019) - Ge, Jun; Zhou, Quan; Niu, Junjie; Wang, Yingjie; Yan, Qi; Wu, Cenhao; Qian, Jiale; Yang, Huilin; Zou, Jun
Abstract : Melatonin, a neuroendocrine hormone secreted by the pineal body, has a positive effect on intervertebral disc degeneration. The present study is aimed at investigating the biological role of melatonin in intervertebral disc degeneration and its underlying mechanism. A human nucleus pulposus cell (NPC) line was exposed to melatonin at different concentrations. Cell proliferation was measured by CCK-8 assay. Cell cycle and apoptosis were analyzed by flow cytometry. Western blot was performed to measure the protein expression of indicated genes. A rabbit model of intervertebral disc degeneration was established to detect the role and mechanism of melatonin on intervertebral disc degeneration. Our study showed that melatonin promoted NPC viability and inhibited cell arrest. Furthermore, melatonin treatment led to the upregulation of collagen II and aggrecan and downregulation of collagen X. Moreover, melatonin significantly elevated the activity of the ERK signaling pathway. Inhibition of the ERK1/2 signals reversed the role of melatonin in the regulation of NPCs both in vitro and in vivo . Melatonin increased NPC viability through inhibition of cell cycle arrest and apoptosis. Moreover, melatonin promoted the secretion of functional factors influencing the nucleus pulposus cell physiology and retarded cell degeneration. Our results suggest that melatonin activated the ERK1/2 signaling pathway, thereby affecting the biological properties of the intervertebral disc degeneration.